2016
DOI: 10.15199/28.2016.4.9
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the fatigue damage development using ESPI method

Abstract: Fatigue damage process developing in structural materials under long-term cyclic loading is still an unsolved problem of modern engineering. Attempts to assess a degree of materials degradation under fatigue conditions on the basis of changes in the areas of local strain concentration determined by optical methods can be treated as the promising contemporary research direction of majority of scientific centers in the world. In most cases, fatigue damage has a local character and it is based on damage developme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…The methods used for damage detection in lap joints include well established Non-Destructive Testing (NDT) approaches, such as: ultrasonic testing [ 18 ], eddy current [ 19 , 20 ], acoustic emission [ 21 , 22 ] and thermography [ 23 , 24 ]. They also include more novel techniques, such as: electronic scanning-laser Doppler vibrometry [ 25 ], speckle-pattern interferometry [ 26 ], electromechanical impedance [ 27 ], the Comparative Vacuum Monitoring (CVM) technique [ 28 ], vibro-acoustic monitoring [ 29 ] or a combination of some of these techniques [ 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…The methods used for damage detection in lap joints include well established Non-Destructive Testing (NDT) approaches, such as: ultrasonic testing [ 18 ], eddy current [ 19 , 20 ], acoustic emission [ 21 , 22 ] and thermography [ 23 , 24 ]. They also include more novel techniques, such as: electronic scanning-laser Doppler vibrometry [ 25 ], speckle-pattern interferometry [ 26 ], electromechanical impedance [ 27 ], the Comparative Vacuum Monitoring (CVM) technique [ 28 ], vibro-acoustic monitoring [ 29 ] or a combination of some of these techniques [ 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…ESPI technique is based on holographic interferometry in which the laser beam is distracted from the optically rough surface. Because it is capable to detect cracks in actual and residual stress fields [9], this technique has been widely used to monitor deformation on metallic specimens including steel [8] and aluminum [9] as well as AA2124/SiC metal matrix composites [10] or nickel based superalloys [11]. Hence, it has been found to be a promising tool in stress distribution maps determination for P91 steel specimens tested under different states and in their elastic range.…”
Section: Introductionmentioning
confidence: 99%
“…It was found that application of correcting asymmetries or parallel illumination beams could successfully eliminate such measuring issue. ESPI was successfully used to detect the crack initiation in coatings and the delamination occurrence at the coating/substrate interface during the fatigue [20,21]. It should be mentioned, however, that the differences between hard coating and substrate material enable to localise the stress concentrators (hard phases or particles) much easier, than on homogenous material; therefore, the ESPI measurements are relatively easy to perform.…”
Section: Introductionmentioning
confidence: 99%